The influence of nanostructured materials on biointerfacial interactions - Koegler, Koegler (Animo Repository, 2012)
Control over biointerfacial interactions in vitro and in vivo is the key to many biomedical applications: from cell culture and diagnostic tools to drug delivery, biomaterials and regenerative medicine. The increasing use of nanostructured materials is placing a greater demand on improving our understanding of how these new materials influence biointerfacial interactions, including protein adsorption and subsequent cellular responses. A range of nanoscale material properties influence these interactions, and material toxicity. The ability to manipulate both material nanochemistry and nanotopography remains challenging in its own right, however, a more in-depth knowledge of the subsequent biological responses to these new materials must occur simultaneously if they are ever to be affective in the clinic. We highlight some of the key technologies used for fabrication of nanostructured materials, examine how nanostructured materials influence the behavior of proteins and cells at surfaces and provide details of important analytical techniques used in this context. © 2012 Elsevier B.V.